CADASTRAL LEVEL SOIL FERTILITY MAPPING IN KHAIRWADGI-1 MICRO-WATERSHED OF LINGASUGUR TALUK, RAICHUR DISTRICT - RAJESH N. L.; KIRANA KUMARA; V. RAJESH; SATISHKUMAR U; B. K. DESAI (The Bioscan, 2020)
Soil fertility parameter viz., pH, Electrical Conductivity (EC), available macro and micro nutrients were determined in surface soil samples taken at cadastral grid intervals from all mapping units of the Khairwadgi-1 micro- watershed of Lingasugur Taluk and Raichur district under The World Bank assisted KWDP II, Sujala-III project on “support for improved programme Integration in rainfed areas” and having total area of 487.59 ha and lies between 76°22’ - 16°30’ North latitudes and 76°24’- 16°10’ East longitudes and average rainfall of this region is 680 mm. Based on soil analysis, fertility maps were prepared at scale (1:8000) using GIS . The surface soil samples have Soil reaction from neutral (pH 6.5-7.3) to moderately alkaline (pH 7.8-8.4) and electric conductivity was non saline. Organic Carbon content was ranges from low (<0.5%) to medium (0.5-0.75%), available Nitrogen was low in entire micro watershed, Phosphorous and potassium content was medium and available sulphur content also low in entire micro-watershed. The available Iron was deficient (<4.5ppm) to sufficient (>4.5ppm), Manganese content was sufficient, Copper was sufficient (>0.2ppm) and available zinc content was deficient in all the parts of micro-watershed.